THE EFFECT OF INTELLECTUAL CAPITAL ON COMPANY PERFORMANCE AND COMPANY VALUE BEFORE AND DURING COVID-19 PANDEMIC - Fitriaty Fitriaty; Muhammad Haris Saputra; Dessy Elliyana (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
This study aims to examine the effect of Value added Intellectual capital (VAIC) consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) on company performance and company value before and during the Covid-19 pandemic. The sample of this research is companies listed on the Indonesia Stock Exchange for the Mining Industry period 2017-2021. The results of this study before covid HCE, SCE and Size had a negative and significant effect on company performance, CEE and VAIC had a significant positive effect on company performance. VAIC has a positive and significant effect on company value. Meanwhile, when the Covid-19 pandemic CEE had a positive and significant impact on company performance, VAIC had a positive and significant impact on company value.